2014
DOI: 10.1016/j.bbi.2013.07.175
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation in myelination mediated by persistent neuroinflammation: Possible mechanisms in chemotherapy-related cognitive impairment

Abstract: Cognitive impairment is commonly reported as a consequence of chemotherapy and can have considerable impact on everyday life on cancer patients. Thus, it is imperative to have a clear understanding of this phenomenon and the underlying mechanism involved. In the present study we examined the role of neuroinflammation and myelination in chemotherapy-related cognitive impairment. Female Sprague-Dawley rats (12-months old) were used in the study (total n=52, 13rats/group). Rats were randomly assigned to either th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 47 publications
1
60
2
5
Order By: Relevance
“…Rats in the control group received normal saline of equal volume to control for the effects of stress induced by the injection. The dosages selected were based on our previous work [15, 26], which showed that animals tolerated these doses with minimal weight loss, fatigue, or death. Both CMF and normal saline injections were given intraperitoneally once a week for a total of 4 weeks and rats were weighed every other day during the chemotherapeutic regimen.…”
Section: Methodsmentioning
confidence: 99%
“…Rats in the control group received normal saline of equal volume to control for the effects of stress induced by the injection. The dosages selected were based on our previous work [15, 26], which showed that animals tolerated these doses with minimal weight loss, fatigue, or death. Both CMF and normal saline injections were given intraperitoneally once a week for a total of 4 weeks and rats were weighed every other day during the chemotherapeutic regimen.…”
Section: Methodsmentioning
confidence: 99%
“…3). A priori, the genotype effect might be explained by a difference in motor response speed from differential neuromuscular transmission due to a TNFα-mediated effect on myelination (Briones and Woods, 2014). However, this explanation is inconsistent with the lack of an effect of genotype on the fastest 10% of reaction times, and would also not be a plausible reason for the amplified genotype effect seen during sleep deprivation as compared to baseline.…”
Section: Discussionmentioning
confidence: 99%
“…However, neurotoxicity is a frequent accompaniment of cancer chemotherapy 5 . Chemobrain, also known as “chemofog,” is a cognitive impairment consisting of deficits in attention, executive and motor function, memory, and speed of information processing, following chemotherapy for a multitude of cancers 6,7 . These deficits, while usually temporary, can persist for several years after completion of drug treatment in a subgroup (17-34%) of patients and can dramatically affect many aspects of daily living, such as employment, social functioning, and community integration 8 .…”
Section: Introductionmentioning
confidence: 99%